A tale that never loses in the telling: Considerations for the shifting ethnobaseline based on artisanal fisher records from the southwestern Atlantic - Santos, Sergio Ricardo; Chagas Macedo, Marcio Luis; Maciel, Thais Rodrigues; Goncalves Souza, Gabriel Barros; Almeida, Lais da Silva; Fazzano Gadig, Otto Bismarck [UNESP]; Vianna, Marcelo (Univ Estadual Paraiba, Editora-eduep, 2022)
An ethnoichthyological survey was conducted with fishers from traditional communities distributed between the Lakes Region and the northern Fluminense region, in the state of Rio de Janeiro, Brazil. The study was developed based on semi-structured interviews, with fishers with at least 30 years of experience. Fishers were asked about changes noted for the biological communities with which they interact with, such as reports concerning abundance changes, the disappearance of certain species or the insertion of new ones, as well as weight and size changes. The reported ethno-names were confirmed at the specific level whenever possible through photographs and complementary descriptions. Eighty-five fishers aged between 39 to 83 years old were interviewed. Fishing activity times ranged from 30 to 68 years, averaging 40.6 years. Fishers reported differing estimates from what was expected according to the known length-weight relationship for the reported species. In general, length estimates were closer to the expected for medium-sized fish from 0.3 m to 1 m. Sixty-nine ethno-names and their variations were identified, associated with 58 fish categories. Of this total, denominations were associated to 47 local fauna species or genera, while one ethno-name was not linked to any taxonomic identification. This study is the result of research financed by the Brazilian Fund for Biodiversity and the Pescarte Environmental Education Project, a mitigation measure required by the Federal Environmental Licensing, conducted by IBAMA.
Keywords: Ethnoknowledge; Small scale fisheries; Common names